If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 3) = -13 Reorder the terms: 4(3 + x) = -13 (3 * 4 + x * 4) = -13 (12 + 4x) = -13 Solving 12 + 4x = -13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 4x = -13 + -12 Combine like terms: 12 + -12 = 0 0 + 4x = -13 + -12 4x = -13 + -12 Combine like terms: -13 + -12 = -25 4x = -25 Divide each side by '4'. x = -6.25 Simplifying x = -6.25
| 0.40x+0.15(240-x)=0.25(240) | | 2(2x-1)=3(4x+2) | | 115+x+x=180 | | 4x-(9-3x)=13(2m-3) | | -8(5+-4)+t=32 | | 5+2.5(x+2)=4.5x-4 | | 0.16(y-6)+0.18y=0.14-0.03(60) | | -3r-1=9r+23 | | 8x-4-2x=10 | | 4x-2(3x)=5 | | 5x-24-11x=3x+24+3x | | -3x+-8+4x=17 | | 2(4x-12)=6(3x-4) | | 0.60x+0.45(120)=0.30(134) | | 2x^2=6-6x | | 44=-2(-4+4x)+2(x-6) | | -10=2x+6 | | 3x-27=4x+8 | | 2-15n=5(-3+2) | | 3(3x+4)=4(2x-2) | | 3x-27=4x-8 | | -10=2x+10 | | =-625-150-(-10) | | 102=6(d+9) | | 33=3(2-3x) | | 2v+15=5v-3 | | 3(x+8)+3=27 | | 3(3b-7)=24 | | 310=2w+2(2w-7) | | 9x^3+8x^2-144x-128=0 | | =5(-5) | | 5(d-2)+7=65 |